Applying Text Feature Walks Strategy in Higher Education to Improve Students’ Critical Reading Comprehension - Mutiara Ayu (JET (Journal of English Teaching), 2021)
This study was conducted to investigate the efficacy of text feature walks strategy in helping students in higher education to improve their critical reading comprehension through the expository texts. It also explored the feedback from students related to the implementation of Text Feature Walks in the virtual classroom. There were 40 students of English Education Study Program in a private university becoming the sample in this study and they were equally divided into experimental and control groups. To measure their improvement in reading comprehension, all students were given pre- and post reading tests in the form of multiple choice. The data obtained were analyzed by using paired sample and independent sample t-tests. The results of paired sample t-test showed that there was a significant improvement in reading (Md=33.13, p=0.000) in experimental group. In addition, the result of independent sample t-test indicated that there were significant difference in reading (Md=39.70, p=0.000) of both groups.